Preventive measures for coastal erosion in Cua Lo, Tam Quang commune, Nui Thanh district, Quang nam province :Master thesis Major Coastal Engineering and Management: Code 62-58-02-03 - Hoàng, Thị Linh Giang (Trường Đại học Thủy Lợi, 2020)
This Master programme is supported by NICHE - VNM 106 Project